Hungarian Monitoring, 5 August 1988 . [Magyar rádiófigyelő], 1988. augusztus 5 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Ligachev's speech in Gorky - Soviet troop withdrawals from Afghanistan - Romanian village reorganization - Vienna follow-up talks Domestic Affairs: - London mayor's talks in Budapest - Exceptional meeting of Youth and Sports Committee to discuss young people's problems - Medgyessy meets Young Communist League (KISZ) members - Interview with first secretary of National Council of Trade Unions (SZOT) - Hungarian-language education in Romania - Printers' conference in Békéscsaba Economy: - Situation at Tatabánya Coalmines Külpolitika: - Ligacsov beszéd Gorkijban - Afganisztáni szovjet csapatkivonulás - Romániai területrendezés - Bécsi utótalálkozó Belpolitika - A londoni főpolgármester budapesti tárgyalásai - Ifjúsági és Sportbizottság rendkívüli ülése a fiatalok gondjairól - Medgyessy KISZ-esekkel találkozik - Interjú a SZOT főtitkárával - Magyar nyelvű oktatás helyzete Romániában - Nyomdász ankét Békéscsabán Gazdaság: - A Tatabányai Szénbányák helyzete